Acute toxic effects of methyl alcohol on the rat brain: The protective effects of caffeic acid phenethyl ester - Çevik, Mehmet U?ur; Varol, Sefer; Yücel, Yavuz; Akil, Eşref; Uzar, E.; Kaplan, I.; Feyzi, Demir Caner (Acta Medica Mediterranea, 2014)
Background: Efficiency of caffeic acid phenethyl ester (CAPE) in reducing free radicals generated by oxidative stress has been previously reported. In the present study, the protective effect of CAPE on methyl alcohol (MeOH) induced oxidative damages on rat brain were presented. Methods: The rats were randomly divided into four groups as follows: Control, methotrexate (MTX) alone, MTX+MeOH, and MTX+MeOH+CAPE (CAPE treatment). All animals except the control group were treated with MTX for 7 days. MTX was diluted in sterile saline and administered (0.3 mg/kg/day) intraperitoneally (ip). At the eighth day, MeOH was administered (3gm/Kg) (ip) in MeOH+MTX and CAPE treatment groups. Four hours after MeOH administration in the CAPE group rats were treated with 10 ?mol/kg CAPE (ip), serum physiologic (i.p.) in MeOH+MTX group. After eight hours, rats were anaesthetized and sacrificed. Malondialdehyde (MDA) levels, paraoxonase-1 (PON-1. activity were measured on the cerebral tissue. Results: MTX+MeOH group compared to the MTX alone group; a statistically significant increase in MDA levels (p= 0.042. were detected. In addition, MTX+MeOH group than MTX MTX alone group in led to a statistically significant decrease in PON-1 activity (p= 0.018.. CAPE treatment, significantly decrease in MDA levels was compared with MeOH+MTX (p= 0.001.. However, CAPE treatment caused an increase on PON-1 activity in MeOH group, which was statistically significant (p= 0.009.. Conclusion: Consequently, it was demonstrated for the first time that CAPE prevents acute MeOH intoxication induced brain injury by reducing the increase in lipid peroxidation, and elevating the decrease in PON-1 activity.
Keywords: Cape; Methyl alcohol; Neurotoxicity; Rat brain